2017
DOI: 10.1016/j.visres.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic complications in the cornea

Abstract: Diabetic corneal alterations, such as delayed epithelial wound healing, edema, recurrent erosions, neuropathy/loss of sensitivity, and tear film changes are frequent but underdiagnosed complications of both type 1 (insulin-dependent) and type 2 (non-insulin-dependent) diabetes mellitus. The disease affects corneal epithelium, corneal nerves, tear film, and to a lesser extent, endothelium, and also conjunctiva. These abnormalities may appear or become exacerbated following trauma, as well as various surgeries i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
186
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(221 citation statements)
references
References 218 publications
(350 reference statements)
5
186
1
7
Order By: Relevance
“…Since the intraocular pressure (IOP) was slightly high (range 23–28 mm Hg) in three of the seven eyes, and normal (14–19 mm Hg) in the remaining four eyes, the Descemet folds were not related to hypotony. It has been reported that various corneal complications including endothelial dysfunction are observed in patients with DM 15. In addition, all seven eyes with Descemet folds in our study had severe inflammatory findings such as fibrin formation (six eyes) and/or 3+ or greater anterior chamber cells (four eyes).…”
Section: Discussionsupporting
confidence: 46%
“…Since the intraocular pressure (IOP) was slightly high (range 23–28 mm Hg) in three of the seven eyes, and normal (14–19 mm Hg) in the remaining four eyes, the Descemet folds were not related to hypotony. It has been reported that various corneal complications including endothelial dysfunction are observed in patients with DM 15. In addition, all seven eyes with Descemet folds in our study had severe inflammatory findings such as fibrin formation (six eyes) and/or 3+ or greater anterior chamber cells (four eyes).…”
Section: Discussionsupporting
confidence: 46%
“…Insulin growth factor 1(IGF1) and its receptor (IGF1-R) are key modulators during various vital cellular processes including cellular differentiation, proliferation, survival and metabolism in various array of cell types (Ljubimov, 2017). They are also known to play a role in DM as well as diabetic keratopathy (Ljubimov, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…They are also known to play a role in DM as well as diabetic keratopathy (Ljubimov, 2017). In this study we found significant upregulation of IGF1 expression in T2DM control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Though the cornea appears normal, significant biochemical changes occur which alter the function of cornea. Advanced glycation end products (AGEs) [1][2][3][4] and matrix metalloproteinases (MMP) have been proposed to be the cause for corneal damage. The accumulation of AGEs enhanced the apoptosis of retinal pericytes, corneal endothelial cells, neuronal cells, and renal mesangial cells.…”
Section: Introductionmentioning
confidence: 99%